Pumping Up the Base: Deployment of Strong Emotion and Simple Language in Presidential Nomination Acceptance Speeches - Whissell, Cynthia (Frontiers in Communication, 2021)
Background and Method: This research examines the nomination acceptance speeches of US presidential candidates from Republican and Democratic parties in the post-WWII mass communication era (1948-2020, 38 speeches). Variables studied are the emotional tone of the speeches, their abstractness, their Grade Level, their employment of personal pronouns and their mentions of “America”. Speeches were scored with the Dictionary of Affect in Language (a sentiment analysis tool). Predictions: On the basis of functionalist theories of political discourse, it was predicted that the speeches would have a pleasant and active or celebratory emotional tone. Based on related research that focused on the effects of mass distribution on presidential communications, it was predicted that the speeches would increase in pleasantness, arousal and linguistic simplicity across years. Results: As predicted, speeches were pleasant and active in tone. Across years, speeches became significantly more arousing, less abstract, simpler, and longer. When individual speeches were divided into five equal portions, a strong significant quadratic trend was observed for pleasantness, which started high at the beginning of a speech, fell in the center, and rose again at the end. Conclusions: Presidential nomination acceptance speeches are emotionally pleasant and active and linguistically simple (Grade 8 level). Between 1948 and 2020, they remained pleasant, and became more active and simpler. In service of their aim to “pump up the base” individual speeches began on a pleasant, nationalistic and personal note, encompassed duller and more impersonal material in their centers, and became positive again at the end.